Wishful thinking or effective threat? tightening bank resolution regimes and bank risk-taking - Magdalena Ignatowski; Josef Korte (European Central Bank (ECB), 2014)
We propose a framework for testing the effects of changes in bank resolution regimes on bank behaviour. By exploiting the differential relevance of recent changes in U.S. bank resolution (i.e., the introduction of the Orderly Liquidation Authority, OLA) for different types of banks, we are able to simulate a quasi-natural experiment using a difference-in-difference framework. We find that banks that are more affected by the introduction of the OLA (1) significantly decrease their overall risk-taking and (2) shift their business model and loan origination towards lower risk, indicating the general effectiveness of the regime change. This effect, however, does (3) not hold for the largest and most systemically important banks. Hence, the introduction of the OLA in the U.S. alone does not appear to have solved the too-big-to-fail problem and might need to be complemented with other measures to limit financial institutions' risk-taking.
Keywords: G21; G28; G33; 330; bank behavior; bank insolvency; bank resolution; FDIC; Orderly Liquidation Authority; risk-taking